Peran Kepemimpinan Transformasional dan Motivasi Pada Kinerja yang dipengaruhi Kesiapan Berubah - Herni Nurtini; Deden Sutisna (Penerbit Goodwood, 2025)
Purpose: To determine the role of Transformational Leadership, Motivation to organizational performance mediated by Readiness to Change Methodology/approach: This research uses quantitative research methods The number of samples based on the Yount table for a population of 101 -1000 the number of samples is 10% in this study a sample of 60 respondents from 141 employees. In this study, random sampling technique was used. This research uses the Smart PLS program 4.0 program and uses analytical methods in the form of validity tests, reliability tests, R-square tests, and hypothesis testing. Results/findings: readiness to change does not mediate transformational leadership and motivation to performance; transformational leadership has a significant effect on readiness to change, motivation has a significant effect on readiness to change and performance. Conclusions: This study found that transformational leadership only influences readiness to change, while motivation affects both employee performance and readiness to change. Readiness to change has no effect on performance nor serves as a mediating variable. Limitations: this research is only limited to the Department of Communication and Informatics so that the results cannot be generalized. Contribution: This study proves that transformational leadership greatly affects the readiness of employees to face change, the need to increase transformational leadership training to increase the expertise of leaders in directing employees to achieve organizational goals.